2019
DOI: 10.1136/jclinpath-2019-205818
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of p16 and PD-L1 expression in patients with oropharyngeal squamous cell carcinoma receiving a definitive treatment

Abstract: AimsLimited information is available regarding the precise differences in the tumour immune microenvironment (TIM) of patients with human papilloma virus (HPV)-associated and non-HPV-associated oropharyngeal squamous cell carcinoma (OPSCC). Here, we retrospectively reviewed 137 patients with OPSCC treated with a definitive treatment to identify molecular relationships in the TIM.Materials and methodsWe used immunohistochemical analysis to assess p16 status, programmed death ligand 1 (PD-L1) level, and/or CD8+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 30 publications
6
37
1
Order By: Relevance
“…In accordance with previous reports, 22,31 we found a significant association between p16 expression and levels of PD-L1 expression on TCs and ICs, as well as between PD-L1 expression on ICs and CD8 + T-cell density. We showed differences between type I TIMs in p16 + tumors and type II TIMs in p16-tumors, which is consistent with the previous report.…”
Section: F I G U R Esupporting
confidence: 93%
See 2 more Smart Citations
“…In accordance with previous reports, 22,31 we found a significant association between p16 expression and levels of PD-L1 expression on TCs and ICs, as well as between PD-L1 expression on ICs and CD8 + T-cell density. We showed differences between type I TIMs in p16 + tumors and type II TIMs in p16-tumors, which is consistent with the previous report.…”
Section: F I G U R Esupporting
confidence: 93%
“…TIL density; type III: TC-PD-L1+/ low CD8 + TIL density; and type IV: TC-PD-L1−/high CD8 + TIL density), as previously reported 22. Types I, II, III, and IV were found in 11 (17%), 15 (23%), 39 (60%), and 0 patients (0%), respectively.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…14,30) However, no worldwide consensus value for the PD-L1 expression is currently present, and there have been reports with diverse criteria of PD-L1 positivity ranged from 5% to even 20%. 25,31) In this study, we used IRS for determining the positivity of PD-L1 expression, because we thought that there should be consideration not only about stained range but also about intensity to rule out the false positive results on interpretation of IHC staining. This IRS method would be an arguable point in our study also with the scoring performed by a single pathologist, however, we sought to minimize above errors by repetitive meticulous examination on multiple slides from specimens with blinded clinical information to the head and neck specialized and experienced pathologist.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nickel has also been shown to induce the silencing of p16 through CpG site hypermethylation and thereby escape cell senescence [44]. Specifically, using p53 heterozygous mice and Wistar rats, treatment with nickel sulfide promoted promoter hypermethylation of p16, a cyclin-dependent kinase inhibitor and tumor suppressor gene [49]. Previous studies have demonstrated that nickel induces site-specific DNA hypermethylation.…”
Section: Dna Hypermethylationmentioning
confidence: 99%